Molecular interactions between 3, 4-dihydroxyphenylglycol and pectin and antioxidant capacity of this complex in vitro. (1st October 2018) - Bermúdez-Oria, Alejandra; Rodríguez-Gutiérrez, Guillermo; Rodríguez-Juan, Elisa; González-Benjumea, Alejandro; Fernández-Bolaños, Juan
Highlights: The existence of the DHPG-pectin complex was confirmed by MALDI TOF-TOF analysis. The formation of non-covalent bonds have been suggested. The formation of covalent bonds (as ester bonds) have been also involved. DHPG-pectin complex encapsulation beads are a good system for colon targeting. DPPH assays confirmed the DHPG-pectin complex's antioxidant activity. Abstract: This study explored the interaction of pectin with 3, 4-dihydroxyphenylglycol (DHPG), a potent phenolic antioxidant naturally found in olive fruit, via encapsulation into pectinate beads. MALDI TOF-TOF analysis supported the formation of complexes between DHPG and pectin. A combination of covalent bonds (ester bonds) and non-covalent interactions, mostly hydrogen bonding, were suggested as the cause of DHPG-pectin complex formation. Free radical scavenging assays confirmed that DHPG maintained its antioxidant activity after complexation and after a digestion simulated in vitro with gastric and intestinal fluids. Therefore, DHPG-pectin beads could reach the large intestine and contribute to a healthy antioxidant environment.